Tumor‐associated macrophages secrete CC‐chemokine ligand 2 and induce tamoxifen resistance by activating PI3K/Akt/mTOR in breast cancer. Issue 1 (19th December 2019) - Li, Dongbo; Ji, Hongfei; Niu, Xingjian; Yin, Lei; Wang, Yiran; Gu, Yucui; Wang, Jinlu; Zhou, Xiaoping; Zhang, Han; Zhang, Qingyuan
Abstract: Breast cancer is the most prevalent malignancy among women. Although endocrine therapy is effective, the development of endocrine resistance is a major clinical challenge. The tumor microenvironment (TME) promotes tumor malignancy, and tumor‐associated macrophages (TAM) within the TME play a crucial role in endocrine resistance. Herein, we aimed to elucidate the relationship between TAM and the endocrine‐resistant phenotype of breast cancer. Macrophages were cultured with conditioned medium (CM) from tamoxifen‐sensitive (MCF7‐S) or ‐resistant (MCF7‐R) MCF7 breast cancer cells. M2 polarization was detected by CD163 immunofluorescence. To determine the effect on endocrine resistance, MCF7 cells were cultured in the supernatant of different TAM, and then treated with tamoxifen. CC‐chemokine ligand 2 (CCL2) immunohistochemistry was carried out on pathological sections from 100 patients with invasive estrogen receptor‐positive breast cancer. We found that macrophages cultured in the CM of MCF7‐S and MCF7‐R cells were induced into TAM, with a more obvious M2 polarization in the latter. Tamoxifen resistance was increased by culture in TAM medium. TAM secreted CCL2, which increased endocrine resistance in breast cancer cells through activation of the PI3K/Akt/mTOR signaling pathway. High expression of CCL2 was correlated with infiltration of CD163+macrophages (r = 0.548, P < .001), and patients with high CCL2 expression presented shorter progression‐free survival than those with low CCL2 expression ( P < .05). We conclude that CCL2 secreted by TAM activates PI3K/Akt/mTOR signaling and promotes an endocrine resistance feedback loop in the TME, suggesting that CCL2 and TAM may be novel therapeutic targets for patients with endocrine‐resistant breast cancer. Abstract : This study investigated the mechanisms underlying tumor‐associated macrophage (TAM)‐mediated endocrine resistance in breast cancer cells. We found that endocrine‐resistant breast cancer cells can induce M2 polarization of TAM, and M2‐polarized TAM in turn further promote endocrine resistance in breast cancer cells. We believe that this article will be of interest to the readership of this journal because we uncovered the underlying mechanism of TAM‐induced endocrine resistance: TAM secrete the cytokine CCL2, which activates the PI3K/Akt/mTOR signaling pathway.